Techno-Economic Feasibility Analysis of Rooftop Solar Power Plant Implementation Based on Electricity Consumption Patterns and kWh Export Schemes - I Made Agus Sudiartha; Putu Sugiartawan; Aniek Suryanti Kusuma (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
This study aims to analyze the techno-economic feasibility of implementing rooftop solar power plants based on electricity consumption patterns and kWh export schemes. The data used comes from the Kaggle dataset